Evaluation of cases with impaired state of consciousness: Gaziantep Children’s Hospital experience - Yiş, Uluç; Yüksel, Çiğdem Nükhet; Köse, Ahmet; Erdoğan, Serpil (The Turkish Journal of Pediatrics, 2012)
The aim of this study was to characterize the etiology, course and prognosis in children admitted to a pediatric intensive care unit (PICU) of Gaziantep Children’s Hospital for impaired state of consciousness. Three hundred and eighty cases were evaluated. Convulsions (44%; n=170) were the leading cause of the impaired state of consciousness followed by poisonings, envenomation, infection, metabolic disease, electrical injury, hepatic encephalopathy, intracranial hemorrhage, brain tumor, and drowning. The diagnosis was definite in 95% (n=359) and probable in 5% (n=21) of cases. Twenty-seven (7%) patients died with impaired state of consciousness. We suggest that defining the causes of impaired state of consciousness in a specific region will help physicians to evaluate the patients faster and in a more systemic manner. Since most of the causes seem to be preventable, appropriate education programs and policies should be provided for improving sanitation and socioeconomic conditions.